Modified PWM Technique for Harmonic Reduction. (11th June 2012) - Hoseinpour, Alireza; Ghazi, Reza
Abstract : This paper presents a Shunt Active Filter (SAF) based on the Variable Index Pulse Width Modulation approach. In the proposed method of Pulse Width Modulation (PWM), the triangular wave is derived by integration of the reference signals. This method introduces two basic advantages; the first one is that the triangular signal contains the information of the signal to be obtained in output and the second advantage is that its amplitude is varied in proportion to the amplitude of the reference signal. Therefore, in this PWM method, the modulation index is varied according to the variation of the reference signal, so it is termed as Variable Index Pulse Width Modulation. In order to demonstrate the validity of the proposed method, the obtained simulation results are compared with results of the Space Vector Modulation (SVM) approach. Furthermore, it is shown that in the case of nonsinusoidal voltages, the SAF with the proposed control strategy can provide the filtering action. This method is quite easy to implement and requires lower circuitry. The results show that the proposed method can satisfy the IEEE-519 standard regarding the reduction of harmonics.